Bridging Skill and Task-Oriented Reading. Issue 1 (2nd January 2017) - Higgs, Karyn; Magliano, Joseph P.; Vidal-Abarca, Eduardo; Martínez, Tomas; McNamara, Danielle S.
Abstract : Some individual difference factors are more strongly correlated with performance on postreading questions when the text is not available than when it is. The present study explores if similar interactions occur with bridging skill, which refers to a reader's propensity to establish connections between explicit text during reading. Undergraduates read science texts using two research tools. The Reading Strategy-Assessment Tool provided a measure of bridging skill. Texts and postreading questions were presented in Read&Answer, and the availability of the text while answering was manipulated. Contrary to prior research, bridging skill was comparably correlated with performance in both availability conditions. Although bridging skill was not correlated with search decisions, there was a trend toward a positive correlation with search time, suggesting that readers who tend to bridge more may also tend to persist longer in searching for answers. The results are discussed in terms of dynamic perspectives of task-oriented reading.